223k views
3 votes
If f(x) = - x2 + 6x - 1 and g(x) = 3x2 - 4x - 1, find (f- g)(x).

2 Answers

2 votes

Answer:


\fbox{\begin{minipage}{11em}(f - g)(x) = -2x(2x - 5)\end{minipage}}

Explanation:

Given:


f(x) = -x^(2) + 6x - 1 \\ g(x) = 3x^(2) - 4x - 1\\

Solve for:


(f - g)(x)

Solution:

Perform the subtraction:


(f - g)(x) = (-x^(2) + 6x - 1) - (3x^(2) - 4x - 1)

Eliminate the parenthesis (notice the change in sign of some components):


(f - g)(x) = -x^(2) + 6x - 1 - 3x^(2) + 4x + 1

Rearrange the expression:


(f - g)(x) = (-x^(2) - 3x^(2)) + (6x + 4x) + (1 - 1)

Simplify the expression:


(f - g)(x) = -4x^(2) + 10x

Perform the inverse of associative property:


(f - g)(x) = -2x(2x - 5)

Hope this helps!

:)

User Geekoverdose
by
4.9k points
2 votes

Answer:

Explanation:

- 4x² + 10x

User Pavel Bastov
by
4.4k points